Patologi Sosial dalam Novel Kado Terbaik Karya J.S. Khairen dan Relevansinya dengan Kejahatan di Indonesia - Ramandanti, Safitri; Muharudin, Eko (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Literary works are a result of the creativity of a literati, literary works can be in the form of novels, poems, and so on. This study examines social pathology in the novel Best Gift by J.S. Khairen. This study uses the study of literary sociology. Sociology discusses how a science in which is discussed how people's lives. Literary sociology is a science that links literary works with sociology. In research conducted in the novel Best Gift by J.S Khairen, the social symptoms studied are bad social behavior. In the novel Best Gift by J.S Khairen, it describes how the social dynamics experienced by the main character. This study aims to describe the form of social pathology and the factors that influence the occurrence of social pathology in the novel Best Gift by J.S. Khairen. This research data is in the form of sentence quotes which are forms or factors of social pathology in the Best Gift novel by J.S. Khairen. Data collection techniques use reading techniques and recording techniques. Data analysis techniques use data reduction, data presentation, and drawing conclusions. This research data validity technique uses theory triangulation. From this study found the form of social pathology and the factors affecting it. Forms of social pathology in J.S. Khairen's novel Best Gift include child exploitation, child abuse, fraud, drug sales, theft, kidnapping, and drug sales. The factors that influence social pathology in the novel Best Gift by J.S. Khairen are family, social environment, economic and educational factors. Keywords:novel best gift, literary sociology, social pathology.